PELATIHAN IMAM DAN KHATIB PROFESIONAL UNTUK MENINGKATKAN KUALITAS IBADAH DAN DA’WAH DI MADRASAH ALIYAH KHAIRUL UMMAH - Malik Husin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Professional training for imams and khatibs is a strategic initiative aimed at improving the quality of religious services and the effectiveness of da’wah within educational settings. The objective of this training is to enhance participants’ competencies in Quranic recitation, understanding of worship jurisprudence (fiqh), da’wah rhetoric, & self-confidence in delivering communicative and inspirati onal sermons. The training methods include lectures, hands-on practice, sermon simulations, and continuous evaluation. The traini ng participants are selected students with potential in religious fields. The results of this activity demonstrate an improvement in the partici pants’ ability to lead prayers with proper recitation and accuracy, as well as to deliver sermons with a systematic structure, clear langua ge, and messages relevant to the congregation’s needs. Thus, the professional imam and khatib training makes a positive contribution to shaping a young generation that is competent in religi ous matters and capable of becoming effective agents of da’wah in the community. It is hoped that this activity will continue and become a flagship program in the development of students’ religious character